ANALISIS SEMIOTIKA FOTO HEADLINE HARIAN DI’S WAY JULI 2020 - Ambat, Yeremia Tulude; Lesmana, Fanny; rianty, asthara (Sintesa, 2024)
Daily DI's Way, a print media that was first published on July 4, 2020, was initiated by a former senior Jawa Pos official, Dahlan Iskan. The main focus of this media is news especially the city of Surabaya. There are three main elements in DI's Way Daily, especially on the main page, namely: text, photos / illustrations, and layout. In the photojournalism aspect, researcher analyze how the message is conveyed through photo headlines and captions on the main page of DI's Way Daily through Roland Barthes' semiotic method, using a qualitative approach. Researcher find the implicit picture of the photo headlines and captions of DI'sWay Daily related to the Surabaya City Government July 2020, the first month this media operates. The results of this study provide an overview of the application of social control values carried out by DI's Way Daily, especially in reviewing the Surabaya City Government program. The topic of the City Government's unpreparedness and inadequate handling of Covid-19 pandemic is one of the most highlighted by this daily on July, 2020. The lack of realization of the Surabaya City Government's programs related to education, transportation and infrastructure is also highlighted on the main page. Keywords: Newspaper, Photojournalism, Semiotic, Roland Barthez, Surabaya City Government